2002
DOI: 10.1002/jmv.10281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple herpesvirus infections on the progression of HIV disease in a cohort of HIV seroconverters

Abstract: The effects of herpesviruses infection on the progression of HIV disease remain controversial, with some studies showing accelerated progression and others showing no effect. Furthermore, the effect of concurrent infection with more than one herpesvirus on the progression of HIV disease has never been investigated. To this end, the rates of progression of HIV disease were determined after stratifying for the presence of up to five different herpesvirus infections. The study population consisted of 359 HIV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Some epidemiological studies have also found a positive correlation between KSHV coinfection and progression to AIDS, suggesting that KSHV may likewise influence the biology of HIV (11,12). Indeed, KSHV infection of HIV-infected monocytic cell lines or peripheral blood mononuclear cells isolated from HIV-infected individuals induces HIV reactivation from a latent state (13).…”
mentioning
confidence: 99%
“…Some epidemiological studies have also found a positive correlation between KSHV coinfection and progression to AIDS, suggesting that KSHV may likewise influence the biology of HIV (11,12). Indeed, KSHV infection of HIV-infected monocytic cell lines or peripheral blood mononuclear cells isolated from HIV-infected individuals induces HIV reactivation from a latent state (13).…”
mentioning
confidence: 99%
“…An effective HSV-1 live-virus vaccine may reduce the incidence of multiple serious diseases, including some cases of genital ulcer disease, thereby reducing the rates of HIV acquisition and transmission (37).…”
Section: Discussionmentioning
confidence: 99%
“…Complications of HSV infection include meningitis, encephalitis, esophagitis, disseminated disease in neonates and immunocompromised individuals, and herpes stromal keratitis, which can lead to blindness. Additionally, HSV-2 infection increases human immunodeficiency virus (HIV) acquisition and transmission rates more than twofold, enhances HIV replication, and speeds progression to AIDS (7,18,37). Despite the significant morbidity and mortality associated with HSV infections, no effective vaccines are available.…”
mentioning
confidence: 99%
“…1 On the other hand, it is growing evidence that herpevirus infection may increase an pasienal's susceptibility to HIV infection, 2 and could interact with HIV to accelerate disease progression. 3,4 To date, there are eight known human herpes viruses, they are herpes simplex virus type 1 (HSV-1), HSV-2, varicella-zoster virus (VZV), and cytomegalovirus (CMV), Epstein-Barr virus (EBV) and human herpesvirus-6, human herpesvirus-7, and HHV-8 (Kaposi's sarcoma herpes virus). 5 Among herpesviruses family members, HSV is the most common co-infection and pathogenic in HIV-1-positive patients.…”
Section: Introductionmentioning
confidence: 99%